Impact of High Diversity of Achromobacter Populations within Cystic Fibrosis Sputum Samples on Antimicrobial Susceptibility Testing - Dupont, Chloé (J Clin Microbiol, 2016)
Chronic colonization by opportunistic environmental bacteria is frequent in the airways of cystic fibrosis (CF) patients. Studies of Pseudomonas aeruginosa evolution during persistence have highlighted the emergence of pathoadaptive genotypes and phenotypes, leading to complex and diversified inpatient colonizing populations also observed at the intraspecimen level. Such diversity, including heterogeneity in resistance profiles, has been considered an adaptive strategy devoted to host persistence. Longitudinal genomic diversity has been shown for the emergent opportunistic pathogen Achromobacter, but phenotypic and genomic diversity has not yet been studied within a simple CF sputum sample. Here, we studied the genomic diversity and antimicrobial resistance heterogeneity of 132 Achromobacter species strains (8 to 27 strains of identical or distinct colonial morphotypes per specimen) recovered from the sputum samples of 9 chronically colonized CF patients. We highlighted the high within-sample and within-morphotype diversity of antimicrobial resistance (disk diffusion) and genomic (pulsed-field gel electrophoresis) profiles. No sputum sample included strains with identical pulsotypes or antibiotic susceptibility patterns. Differences in clinical categorization were observed for the 9 patients and concerned 3 to 11 antibiotics, including antibiotics recommended for use against Achromobacter. Within-sample antimicrobial resistance heterogeneity, not predictable from colonial morphology, suggested that it may represent a selective advantage against antibiotics in an Achromobacter persisting population and potentially compromise the antibiotic management of CF airway infections.